PEMBELAJARAN BERASASKAN PROJEK SEBAGAI PEDAGOGI ALTERNATIF: SATU KAJIAN RESTROSPECTIVE - A/P Arunachalam, Chitradevi A/P Arunachalam (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract The Ministry of Education has decided to replace the subject to the study subjects n history in all schools from 2014for pupil sin the sphereumur10fouryears. It is in line with the governments decision to make the subjects of history as a compulsory subject topassin the Certificate of Education Malaysia by 2012.This paper aims to identify appropriate ways to teach history according to the level of childrens brains. The subjectsusuallytaughthistoryatages13and older. But now hebegan teaching at the age of10years. The refore this study aims to look at the use of project-based learning in the subjects o fhis toryin a Tamil national type schools. The concept paper that the level o fenrollmenton the use oft he project contribute in improving student achievement in the subjects of history